Karakteristik Fisikokimia Mi Instan Bebas Gluten Berbasis Labu Kuning (Curcubita maxima) - Chapib Jamaludin; Iffah Muflihati; Arief Rakhman Affandi (Universitas PGRI Yogyakarta, 2025)
Pumpkin is an abundant agricultural commodity that has not been utilised to its full potential. People's consumption patterns that are moving towards gluten-free processed foods are an opportunity for the development of processed pumpkin products. Instant noodles are one of the processed products that are in demand by the public. This study aims to determine the physicochemical characteristics of gluten-free pumpkin instant noodles. Gluten-free pumpkin instant noodles were tested proximate, colour and texture. This research used experimental method with 1 type of instant noodle formulation. The results of this study showed that gluten-free pumpkin instant noodles contained protein content of 4.87% protein, 4.09% water content, 19.47% fat content, 4.03% ash content, and 67.32% carbohydrate content. Texture analysis included hardness, stickiness and tackiness with values of 13.42 N, 0.03 mJ, and 4.62 N, respectively. Colour values showed a brightness of 53.29 with the colour of the noodles tending to brown.